2020
DOI: 10.35333/jrp.2020.198
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of phenolic compounds and protective effects of olive (Olea europaea L.) leaf extracts on endothelial cells against hydrogen peroxide-induced toxicity

Abstract: How to cite this article: Torul H, Küçükboyacı N, Tamer U, Karasu Ç. Evaluation of phenolic compounds and protective effects of olive (Olea europaea L.) leaf extracts on endothelial cells against hydrogen peroxide-induced toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…As shown in ( Figure 5 ), the HT, DHPG extracts, and their mixture did not show any growth inhibition effects in human cells in a dose-dependent way. The capacity of HT to protect healthy cells has been reported in other studies where it was observed that HT presented a viability of more than 60%, even when they had undergone previous oxidation with H 2 O 2 [ 29 ]. In fact, the anti-proliferative capacity of HT has been reported in other unhealthy cell lines such as HeLa and DG75 [ 30 ], which was very promising in the fight against neurodegenerative diseases.…”
Section: Resultsmentioning
confidence: 83%
“…As shown in ( Figure 5 ), the HT, DHPG extracts, and their mixture did not show any growth inhibition effects in human cells in a dose-dependent way. The capacity of HT to protect healthy cells has been reported in other studies where it was observed that HT presented a viability of more than 60%, even when they had undergone previous oxidation with H 2 O 2 [ 29 ]. In fact, the anti-proliferative capacity of HT has been reported in other unhealthy cell lines such as HeLa and DG75 [ 30 ], which was very promising in the fight against neurodegenerative diseases.…”
Section: Resultsmentioning
confidence: 83%
“…), the elimination of elevated superoxide levels, the reduction in increased NADPH oxidase activity, and the activation of antioxidant cell proteins such as SIRT1 and peroxisome proliferator-activated receptor-γ coactivator-1α (PGC-1α) [ 25 , 104 , 105 , 106 ]. Moreover, olive leaf polyphenolic compounds oleuropein and hydroxytyrosol are efficient cytoprotective agents against H 2 O 2 -induced oxidative stress and toxicity in human umbilical vein endothelial cells [ 107 ].…”
Section: Anti-stroke Action Of Olive Polyphenolsmentioning
confidence: 99%
“…The molecular action of HT downregulates NFκB pathway which improves NO production. HT also promote cellular survival from ROS induction (Torul et al, 2020). These series of evidence, allow us to proposed HT that could promote reendothelization in the site of endothelial injury.…”
Section: Discussionmentioning
confidence: 88%
“…In addition to that, HT also protect cells from H 2 O 2 induced cytotoxicity and apoptosis by decreasing superoxide release (Nakbi et al, 2011;Torul et al, 2020) while activating JNK and p38 MAPKs pathways (Kitsati et al, 2016). Interestingly, a particular study by Zrelli found that HT activate the AMPK-FOXO3 pathway by enhancing catalase activity to reduce oxidative stress (Zrelli et al, 2011b).…”
Section: Ht Role As An Antioxidantmentioning
confidence: 97%
See 1 more Smart Citation